Comparative Efficacy and Safety of Anti-VEGF Agents in Neovascular Age-Related Macular Degeneration: A Meta-Analysis - Ramzi Amin; Siti Pradyta Phiskanugrah (HM Publisher, 2025)
Neovascular age-related macular degeneration (nAMD) is a leading cause of vision loss in the elderly. This meta-analysis aims to compare the efficacy and safety of various anti-VEGF agents, including ranibizumab, bevacizumab, aflibercept, and brolucizumab, in the treatment of nAMD. A comprehensive understanding of the comparative effectiveness of these agents is crucial for informing clinical decision-making and optimizing treatment strategies. A meta-analysis was conducted using electronic databases, including PubMed, Embase, and the Cochrane Central Register of Controlled Trials (CENTRAL), to identify relevant randomized controlled trials (RCTs) published between 2013 and 2024. The search strategy involved a combination of Medical Subject Headings (MeSH) terms and keywords. Two independent reviewers extracted data from the included studies using a standardized form. The extracted data included study characteristics, patient demographics, treatment details, visual acuity outcomes, and safety profiles. Seven RCTs were included in the meta-analysis. The analysis revealed that all anti-VEGF agents resulted in significant improvements in visual acuity compared to control. Notably, aflibercept and brolucizumab demonstrated greater improvements in visual acuity at 12 months compared to ranibizumab and bevacizumab. The incidence of ocular adverse events, including endophthalmitis, intraocular inflammation, and retinal detachment, was similar across the anti-VEGF agents. All anti-VEGF agents are effective in improving visual acuity in nAMD. Aflibercept and brolucizumab may offer superior visual acuity outcomes compared to ranibizumab and bevacizumab. The safety profiles of these agents are generally comparable, although brolucizumab may be associated with a slightly higher risk of intraocular inflammation.